Pengaruh Jumlah Ruas dan Konsentrasi Rootone-F pada Pertumbuhan Setek Kopi Robusta - Salim, Abdurrahman; Erdiansyah, Novie Pranata; Yudha, Bhima Reformana (Politeknik Negeri Lampung, 2022)
Coffee is one of the commodities in Indonesia that excels in exports, and one of the most widely cultivated coffees in Indonesia is robusta coffee. Propagation by segment cuttings on Robusta coffee plants can produce new plants in large numbers and have the same gene characteristics as the parent in a short period. Then there is a growth regulatory administered exogenously (from outside) are an alternative way to accelerate root formation in plants. This study was conducted to determine the effect of the number of segments and concentration of Rootone-F on the growth of robusta coffee cuttings. The research was conducted for three months, from 23 March 2021 to 15 June 2021. The research was conducted at the Kaliwining Gardens, the Coffee and Cocoa Research Center, Jember. The statistical method used was a completely randomized design (CRD) by factorial. The first factor was the number of segments and the second factor was the concentration of Rootone-F; there were 12 treatment combinations and three replications. The results showed that the number of internodes' treatments was significantly different on shoot length, root wet weight, and root dry weight. The concentration of Rootone F was not significantly different for all variables observed.